Analisis Faktor-Faktor yang Mempengaruhi Perkembangan Bisnis di Sektor Kuliner pada Usaha Ayam Kampus Cimahi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research focuses on analyzing the factors influencing the business development of Ayam Kampus Cimahi, a take-away culinary business that serves crispy chicken fillet rice with various sambal and sauce options. The study aims to identify and evaluate internal and external factors affecting business growth, enabling the formulation of more effective development strategies. The research employs a quantitative approach by collecting data through surveys and interviews with customers, as well as direct business operational analysis. The collected data is then analyzed to understand the relationship between variables influencing business performance. The findings indicate that digital marketing strategies, product quality, and competitive pricing significantly impact customer satisfaction and loyalty. Additionally, operational efficiency and responsiveness to changing trends are crucial factors in business sustainability. The conclusion of this study emphasizes that effective business management, product innovation, and the utilization of digital marketing strategies can enhance the competitiveness of Ayam Kampus Cimahi in the local culinary market. The recommendations provided include expanding menu variations, optimizing marketing strategies, and improving operational management to ensure sustainable business growth.